AVALIAÇÃO DE FERIDAS COMPLEXAS EM UM AMBULATÓRIO DE FERIDAS - Santos, Igor Michel Ramos dos; Silva, Davi Porfirio da; Oliveira, Fabianny Torres de; Amorim, Hilma Keyla de; Silva, Paulo Sérgio Gomes da (Gep News, 2020)
Trabalho premiado em PRIMEIRO LUGAR - Comunicação Oral